Encontros Bibli Vol. 19, n. 39 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Encontros Bibli Vol. 19, n. 39 (2014) Link de acesso ao númerohttps://periodicos.ufsc.br/index.php/eb/issue/view/2111/showToc